Potential of Moringa (Moringa oleifera) leaf extract to inhibit the growth of pathogenic bacteria Edwardsiella tarda - Farid Mukhtar Riyadi; Arief Prajitno; Mohamad Fadjar; Arif Syaifurrisal; Annisa Isti Fauziyyah (Department of Aquaculture, 2021)
This study analyzed the antibacterial activity of Moringa oliefera leaf extract against the growth of Edwardsiella tarda bacteria. This study aims to determine the antibacterial activity of Moringa leaf extract (M. oliefera) against the growth of E.tarda bacteria. Inhibition testing is done by diffusion method (disc test). The disc test used five variations of concentration of 75 mg/L, 150 mg/L, 225 mg/L, 300 mg/L, and 375 mg/L on TSA (Tryptone Soya Agar) media and incubated for 2x24 hours. As a positive control, an antibiotic in the form of chloramphenicol was used. (5 mg/L) Moreover, distilled water was used as a negative control.Moringa leaf extract (M. oliefera) contains natural active compounds, bacteriostatic antibacterials, due to decreased bacterial growth after 48 hours of incubation. The highest inhibition diameter of E. tarda was 12.95 mm at a concentration of 375 mg/L after 24 hours incubation and decreased by 11.02 mm after 48 hours incubation. The highest inhibitory effectiveness was at a concentration of 375 mg/L with an effectiveness of 58.8%, while the effectiveness of the decrease was 48.1% after 48 hours of incubation.